POSTNATAL EVALUATION OF PULMONARY ARTERIOLES IN BABY ALPACA - Manrique E., Zarela (2013)
In the postnatal phase in mammalians, the vasodilatation of the pulmonary arterioles is critical, since this will affect the amount of blood passing through the alveoli for oxygenation. The aim of the study was to evaluate the diameter, the thickness of the muscle layer and the relationship muscle layer/arteriolar diameter (CM/DA) as indication of changes in the vascular lumen in the postnatal period of baby alpacas. Lungs of 36 alpacas between 1 to 45 days of age were obtained according to nine age groups (one group each 5 days of age). The lung histological sections were stained with Mallory’s phosphotungstic acid hematoxylin. The arteriolar diameter showed a significant increase (p<0.05) between age groups 1 and 2 versus 7, 8 and 9. The thickness of the muscle layer showed no significant changes between groups, while the CM/DA relationship values decreased with age (groups 1 and 2 were statistical different of groups 6, 7, 8 and 9; p<0.05). It is concluded that the CM/DA relationship decreases and the lumen of pulmonary arterioles increases according to age, and this is due to increased arteriolar diameter (p<0.05) but not to thickness of smooth muscles.